HUBUNGAN PENEMPATAN DAN PENGEMBANGAN PEGAWAI DENGAN PRESTASI KERJA PADA PARDEDE INTERNATIONAL HOTEL MEDAN - Binur Pretty Napitupulu; Ivan Benedict (Akademi Pariwisata Darma Agung, 2019)
The purpose of this research is to analyze between placemet and development the staff with workperformance of the staff Pardede International Hotel Medan. The methode of research which used ismethode of survey with respondent total 40 people, which choosen according of proportional randomsampling. Which using quesioner to collect the variable of data positioning, developmend and good jobperformance. The result of this research find that : 1. There is positif relationship between placement (X¹) with good work performance (Y) withcoefisien corelation ry¹ =0,6767 and regretion equation y = 25,31 + 0,74 X¹ 2. There is positif relationship between development (X²) with good work perpormance (Y) withcorrelation coeficient ry² = 0,7112 and regression equation y= 33,15+0,65X² 3. There is positif relationship between placement (X¹) and development (X²) by doing togetherwith good work performance (Y) with double correlation coeficient Ry 123 = 0,793 and doubleof regression equation y = 10,78 + 0,453 (X¹) + 0,451 (X²) According about that research, the researcher can take the conclusion that good work performance of thestaff Pardede International Medan can improved by the attention about the correct employee placement.(the right man on the right place) accourding with the ability and skill with doing development of the staffto fostering ability of the staff and to create the personality, ability, skill to inovation, initiative anddicipline